Genetic interrogation for sequence and copy number variants in systemic lupus erythematosus - Yeo, Nicholas Kim-Wah; Lim, Che Kang; Yaung, Katherine Nay; Khoo, Nicholas Kim Huat; Arkachaisri, Thaschawee; Albani, Salvatore; Yeo, Joo Guan (Frontiers in Genetics, 2024)
Early-onset systemic lupus erythematosus presents with a more severe disease and is associated with a greater genetic burden, especially in patients from Black, Asian or Hispanic ancestries. Nextgeneration sequencing techniques, notably whole exome sequencing, have been extensively used in genomic interrogation studies to identify causal disease variants that are increasingly implicated in the development of autoimmunity. This Review discusses the known casual variants of polygenic and monogenic systemic lupus erythematosus and its implications under certain genetic disparities while suggesting an age-based sequencing strategy to aid in clinical diagnostics and patient management for improved patient care.